Response of Surface Temperature to Afforestation in the Kubuqi Desert, Inner Mongolia. Issue 2 (29th January 2018) - Wang, Liming; Lee, Xuhui; Schultz, Natalie; Chen, Shiping; Wei, Zhongwang; Fu, Congsheng; Gao, Yunqiu; Yang, Yanzheng; Lin, Guanghui
Abstract: In this study, micrometeorological observations in a shrub ecosystem and an adjacent poplar plantation forest ecosystem in the Kubuqi Desert, Inner Mongolia, China, are used to evaluate the theory of intrinsic biophysical mechanism (IBPM) and to investigate the biophysical effects of afforestation. Results indicate that after forcing energy balance closure to the observed fluxes, the IBPM theory agrees very well with the observed temporal variations in the surface temperature and with the observed temperature difference between the paired sites at the half‐hourly time scale. Afforestation activity in this dryland landscape has a cooling effect (−0.5 ± 0.2 K) in the daytime in all the seasons and a warming effect (0.2 ± 0.1 K) in the nighttime during the winter, spring and, autumn but a cooling effect (−1.0 ± 0.3 K) in the summer at night. These temperature changes are decomposed into contributions from changes in surface albedo, surface roughness, Bowen ratio, and ground heat flux. Comparison is made between the IBPM theory and the theory of the decomposed temperature metric. Key Points: Plantation forest is cooler in the daytime and mostly warmer at night than an adjacent shrub land in Inner Mongolia, China Energy balance closure is an important condition for partitioning of biophysical effects of land use change Biophysical contributions from the surface temperature decomposition metric theory are an order of magnitude greater than the related terms from the intrinsic biophysical mechanism theory